(untitled) (Ius Novum, 2020)
The paper analyses the concept of ‘tendering resignation’ by a voivodship marshal, referred to in Article 38 para. 1 and Article 37 para. 4 of the Voivodship Self-Government Act. The author interpretes the term ‘resignation’, explaining its essence and nature. In the author’s opinion, only the authorised person, i.e. the voivodship marshal, may submit a statement of resignation, which excludes the possibility of doing this by proxy. The Act does not specify the form in which the statement of resignation is made, which means that it can be submitted both in writing and verbally, as well as in the electronic form. Withdrawal of the tendered resignation is allowed, provided that the voting procedure stipulated in Article 38 para. 2 of the Voivodship Self-Government Act has not been commenced. The paper also analyses the procedure to be followed when accepting the resignation tendered by the voivodship marshal and its effects.